THE EFFECT OF LISTENING TO HARSH WORDS ON THE REWARD OF FASTING : A Study Based on the Views of Prof. Dr. Shauqi Ibrahim Allam - Prasetya, Debby Eka; Hafidzi, Anwar (Muta'allim: Jurnal Pendidikan Agama Islam, 2024)
This research aims to examine the fatwa issued by Prof. Dr. Shauqi Ibrahim Allam regarding the influence of listening to rude words on the rewards of fasting in Islam. The research method used is qualitative with a descriptive approach and literature review. The primary data analyzed is the fatwa of Prof. Dr. Shauqi Ibrahim Allam, while the secondary data includes related literature. The analysis is based on the content of the fatwa as well as its historical and theological context, considering its relevance in the modern life context. The research findings are expected to provide a deeper understanding of the Islamic perspective on speech ethics and listening and its implications for fasting worship. This is expected to provide practical guidance for Muslims in conducting fasting worship with full awareness and obedience to religious teachings. Keywords: Influence of listening to rude words, reward of fasting, fatwa of Prof. Dr. Shauqi Ibrahim Allam, Islam, speech ethics and listening, fasting worship Abstrak Penelitian ini bertujuan untuk mengkaji fatwa yang dikeluarkan oleh Prof. Dr. Shauqi Ibrahim Allam mengenai pengaruh mendengarkan perkataan kasar terhadap pahala puasa dalam Islam. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif dan kajian pustaka. Data utama yang dianalisis adalah fatwa dari Prof. Dr. Shauqi Ibrahim Allam, sementara data sekunder meliputi literatur terkait. Analisis dilakukan terhadap isi fatwa serta konteks historis dan teologisnya, dengan mempertimbangkan relevansinya dalam konteks kehidupan modern. Temuan penelitian diharapkan dapat memberikan pemahaman yang lebih mendalam mengenai pandangan Islam terhadap etika berbicara dan mendengar serta implikasinya terhadap ibadah puasa. Hal ini diharapkan dapat memberikan pedoman praktis bagi umat Muslim dalam menjalankan ibadah puasa dengan penuh kesadaran dan kepatuhan terhadap ajaran agama. Kata Kunci: Pengaruh Mendengarkan Perkataan Kasar, Pahala Puasa, Fatwa Prof. Dr. Shauqi Ibrahim Allam, Islam, Etika Berbicara dan Mendengar, Ibadah Puasa